Effect of Biochemical and Physiological Response to Salt Stress in Camelina sativa. Issue 7 (12th April 2017) - Morales, Diego; Potlakayala, Shobha; Soliman, Mario; Daramola, Juliann; Weeden, Hannah; Jones, Andrew; Kovak, Emma; Lowry, Emily; Patel, Pooja; Puthiyaparambil, Josekutty; Goldman, Stephen; Rudrabhatla, Sairam
ABSTRACT: Camelina sativa is a promising low-input, high yielding biodiesel crop that can be suitable to grow on marginal lands and is a good source of omega-3 fatty acids. The objective of the study was to compare the rate of growth in different varieties of C. sativa in response to salt stress. Three biological replicates were collected from three varieties of C. sativa grown in vitro in a controlled growth room. The Blaine Creek, Cheyenne and Suneson varieties of C. sativa were analyzed for their physiological and biochemical response to salt stress using the following criteria: germination rates, measurement of length, dry weights, fresh weights, and stomatal size. The biochemical measurements focused on proline, chlorophyll, and flow cytometry analysis. Blaine Creek's growth during salt stress was overall the most affected, while Suneson and Cheyenne generated higher amounts of biomass, thus indicating that C. sativa can be grown on saline soils.